A case of angle‐closure glaucoma caused by spontaneous lens dislocation. Issue 12 (5th December 2022) - Kondo, Keisuke; Isono, Hiroki
Abstarct: Spontaneous lens dislocation without genetic factors is rare. In this case, spontaneous lens dislocation occurred without an apparent trigger and resulted in secondary angle‐closure glaucoma. A head computed tomography (CT) scan showed lens dislocation. It is critical to assess for lens dislocation during head CT scan for a sudden headache. Abstract : In this case, spontaneous lens dislocation occurred without an apparent trigger. A CT scan of the head showed that the left intraocular lens had deviated posteriorly.